2023
DOI: 10.3390/vaccines11020246
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Situation of HIV and Monkeypox Coinfection: A Systematic Review

Abstract: The most recent monkeypox (Mpox) outbreak is mostly affecting men who have sex with men (MSM) who participate in high-risk sexual behaviors, which is typically the case among human immunodeficiency virus (HIV) carriers, according to clinical and epidemiological statistics. The objective of this research is to determine the epidemiological situation of HIV and smallpox co-infection. Until 1 October 2022, a thorough evaluation of the literature was conducted utilizing the databases PubMed, Embase, Scopus, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 81 publications
1
25
0
Order By: Relevance
“…Before the current mpox outbreak, WHO reported mpox mortality rates of up to 11% [ 49 ]. In addition, at the beginning of the current outbreak, different studies reported that the main affected group was MSM [ 50 ], who have a higher HIV prevalence compared to the general population [ 10 ] and were the predominant group of reported cases with mpox and HIV coinfection [ 45 , 51 , 52 ]. In response, in July 2022, the Peruvian government issued a guideline for the prevention and management of patients with mpox, which considered HIV+ and immunosuppressed patients at risk of developing more severe disease and mpox complications [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the current mpox outbreak, WHO reported mpox mortality rates of up to 11% [ 49 ]. In addition, at the beginning of the current outbreak, different studies reported that the main affected group was MSM [ 50 ], who have a higher HIV prevalence compared to the general population [ 10 ] and were the predominant group of reported cases with mpox and HIV coinfection [ 45 , 51 , 52 ]. In response, in July 2022, the Peruvian government issued a guideline for the prevention and management of patients with mpox, which considered HIV+ and immunosuppressed patients at risk of developing more severe disease and mpox complications [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz-Saavedra B et al reported in their study that 40.32% of cases with MPX had HIV coinfections [ 42 ]. Coinfections with these two viruses are very harmful, as it can aggravate the symptoms of both diseases and make them more difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Before the current mpox outbreak, WHO reported mpox mortality rates of up to 11% [49]. In addition, at the beginning of the current outbreak, different studies reported that the main affected group was MSM [50], who have a higher HIV prevalence compared to the general population [10] and were the predominant group of reported cases with mpox and HIV coinfection [45,51,52]. In response, in July 2022, the Peruvian government issued a guideline for the prevention and management of patients with mpox, which considered HIV + and immunosuppressed patients to be at risk of developing more severe disease and mpox complications [53].…”
Section: Discussionmentioning
confidence: 99%